Despite warming temperatures, hatchery origin Chinook and coho salmon spawn earlier in the fall: a multi-decade analysis - Thomas P. Quinn; Jason Ray; Michael D. Tillotson (Hydrobiologia, 2026)

Evaluating surface fluxes in WRF using eddy-covariance flux measurements in the Western and Eastern U.S. - Fan Wu; Kenneth J. Davis; Li Zhang; Ray G. Anderson; Jason P. Horne; Sarah Goslee; William Munger; Chenxia Cai; Yu Yan Cui; Zhan Zhao; Min Zhong (Agricultural and Forest Meteorology, 2026)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

Does urbanisation lead to parallel demographic shifts across the world in a cosmopolitan plant? - Aude E. Caizergues; James S. Santangelo; Rob W. Ness; Fabio Angeoletto; Daniel N. Anstett; Julia Anstett; Fernanda Baena‐Diaz; Elizabeth J. Carlen; Jaime A. Chaves; Mattheau S. Comerford; Karen Dyson; Mohsen Falahati‐Anbaran; et al. (Molecular Ecology, 2024)
Urbanisation is occurring globally, leading to dramatic environmental changes that are altering the ecology and evolution of species. In particular, the expansion of human infrastructure and the loss and fragmentation of natural habitats in cities is predicted to increase genetic drift and reduce gene flow by reducing the size and connectivity of populations. Alternatively, the ‘urban facilitation model’ suggests that some species will have greater gene flow into and within cities leading to higher diversity and lower differentiation in urban populations. These alternative hypotheses have not been contrasted across multiple cities. Here, we used the genomic data from the GLobal Urban Evolution project (GLUE), to study the effects of urbanisation on non‐adaptive evolutionary processes of white clover ( Trifolium repens ) at a global scale. We found that white clover populations presented high genetic diversity and no evidence of reduced N e linked to urbanisation. On the contrary, we found that urban populations were less likely to experience a recent decrease in effective population size than rural ones. In addition, we found little genetic structure among populations both globally and between urban and rural populations, which showed extensive gene flow between habitats. Interestingly, white clover displayed overall higher gene flow within urban areas than within rural habitats. Our study provides the largest comprehensive test of the demographic effects of urbanisation. Our results contrast with the common perception that heavily altered and fragmented urban environments will reduce the effective population size and genetic diversity of populations and contribute to their isolation.

Metagenomics untangles potential adaptations of Antarctic endolithic bacteria at the fringe of habitability - Claudia Coleine; Davide Albanese; Angelique E. Ray; Manuel Delgado-Baquerizo; Jason E. Stajich; Timothy J. Williams; Stefano Larsen; Susannah Tringe; Christa Pennacchio; Belinda C. Ferrari; Claudio Donati; Laura Selbmann (Science of The Total Environment, 2024)

Pilot evaluation of the potential log removal credit using chemical markers for reverse osmosis and nanofiltration - Hannah Ray; Deena Hannoun; Jason Assouline; Jim Vickers; Eric Dickenson (Desalination, 2024)

Effect of dietary phytase on water and fecal prokaryotic and eukaryotic microbiomes in a hybrid tilapia (Oreochromis aureus x O. niloticus) mixotrophic biofloc production system - Candis L. Ray; Jason W. Abernathy; Bartholomew W. Green; Adam R. Rivers; Kevin K. Schrader; Steven D. Rawles; Matthew E. McEntire; Miles D. Lange; Carl D. Webster (Aquaculture, 2024)

On-Field Deployment and Validation for Wearable Devices - Calvin Kuo; Declan Patton; Tyler Rooks; Gregory Tierney; Andrew McIntosh; Robert Lynall; Amanda Esquivel; Ray Daniel; Thomas Kaminski; Jason Mihalik; Nate Dau; Jillian Urban (Annals of Biomedical Engineering, 2022)
Wearable sensors are an important tool in the study of head acceleration events and head impact injuries in sporting and military activities. Recent advances in sensor technology have improved our understanding of head kinematics during on-field activities; however, proper utilization and interpretation of data from wearable devices requires careful implementation of best practices. The objective of this paper is to summarize minimum requirements and best practices for on-field deployment of wearable devices for the measurement of head acceleration events in vivo to ensure data evaluated are representative of real events and limitations are accurately defined. Best practices covered in this document include the definition of a verified head acceleration event, data windowing, video verification, advanced post-processing techniques, and on-field logistics, as determined through review of the literature and expert opinion. Careful use of best practices, with accurate acknowledgement of limitations, will allow research teams to ensure data evaluated is representative of real events, will improve the robustness of head acceleration event exposure studies, and generally improve the quality and validity of research into head impact injuries.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

The Path to an Ecosystem Approach for Forage Fish Management: A Case Study of Atlantic Menhaden - Kristen A. Anstead; Katie Drew; David Chagaris; Amy M. Schueller; Jason E. McNamee; Andre Buchheister; Geneviève Nesslage; Jim H. Uphoff Jr.; Michael J. Wilberg; Alexei Sharov; Micah J. Dean; Jeffrey Brust; et al. (Frontiers in Marine Science, 2021)
Atlantic menhaden ( Brevoortia tyrannus ) support the largest fishery by volume on the United States East Coast, while also playing an important role as a forage species. Managers’ and stakeholders’ increasing concerns about the impact of Atlantic menhaden harvest on ecosystem processes led to an evolution in the assessment and management of this species from a purely single-species approach to an ecosystem approach. The first coastwide stock assessment of Atlantic menhaden for management used a single-species virtual population analysis (VPA). Subsequent assessments used a forward projecting statistical catch-at-age framework that incorporated estimates of predation mortality from a multispecies VPA while analytical efforts continued toward the development of ecosystem models and explicit ecological reference points (ERPs) for Atlantic menhaden. As an interim step while ecosystem models were being developed, a series of ad hoc measures to preserve Atlantic menhaden biomass for predators were used by managers. In August 2020, the Atlantic States Marine Fisheries Commission formally adopted an ecological modeling framework as a tool to set reference points and harvest limits for the Atlantic menhaden that considers their role as a forage fish. This is the first example of a quantitative ecosystem approach to setting reference points on the United States Atlantic Coast and it represents a significant advance for forage fish management. This case study reviews the history of Atlantic menhaden stock assessments and management, outlines the progress on the current implementation of ERPs for this species, and highlights future research and management needs to improve and expand ecosystem-based fisheries management.

Potential carcinogenic and non-carcinogenic health hazards of metal(loid)s in food grains - Sandip Singh Bhatti; Vaneet Kumar; Anupama Kumar; Jason K. Kirby; John Gouzos; Ray Correll; Jaswinder Singh; Vasudha Sambyal; Avinash Kaur Nagpal (Environmental Science and Pollution Research, 2020)

Governing in the Anthropocene: are there cyber-systemic antidotes to the malaise of modern governance? - Ray Ison; Jason Alexandra; Phil Wallis (Sustainability Science, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Soybean Aphid Response to their Alarm Pheromone E-ß-Farnesene (EBF) - Jaclyn L. Eichele; Jamin Dreyer; Ray Heinz; Stephen P. Foster; Deirdre A. Prischmann-Voldseth; Jason P. Harmon (Journal of Insect Behavior, 2016)

Assessing bee (Hymenoptera: Apoidea) diversity of an Illinois restored tallgrass prairie: methodology and conservation considerations - Ray K. Geroff; Jason Gibbs; Kenneth W. McCravy (Journal of Insect Conservation, 2014)

Iron cycling at corroding carbon steel surfaces - Jason S. Lee; Joyce M. McBeth; Richard I. Ray; Brenda J. Little; David Emerson (Biofouling, 2013)

The muscarinic M1 receptor positive allosteric modulator PQCA improves cognitive measures in rat, cynomolgus macaque, and rhesus macaque - Jason M. Uslaner; Donnie Eddins; Vanita Puri; Christopher E. Cannon; Jane Sutcliffe; Chan Sing Chew; Michelle Pearson; Jeffrey A. Vivian; Ronald K. Chang; William J. Ray; Scott D. Kuduk; Marion Wittmann (Psychopharmacology, 2013)

Sulphide production and corrosion in seawaters during exposure to FAME diesel - Jason S. Lee; Richard I. Ray; Brenda J. Little; Kathleen E. Duncan; Athenia L. Oldham; Irene A. Davidova; Joseph M. Suflita (Biofouling, 2012)

Movement and persistence by Ross’s Geese (Chen rossii) in Canada’s arctic - Ray T. Alisauskas; Kiel L. Drake; Jason H. Caswell; Dana K. Kellett (Journal of Ornithology, 2012)

Linked gene networks involved in nitrogen and carbon metabolism and levels of water-soluble carbohydrate accumulation in wheat stems - C. Lynne McIntyre; Rosanne E. Casu; Allan Rattey; M. Fernanda Dreccer; Jason W. Kam; Anthony F. van Herwaarden; Ray Shorter; Gang Ping Xue (Functional & Integrative Genomics, 2011)

An assessment of alternative diesel fuels: microbiological contamination and corrosion under storage conditions - Jason S. Lee; Richard I. Ray; Brenda J. Little (Biofouling, 2010)

Hydrologic and biotic influences on nitrate removal in a subtropical spring‐fed river - James B. Heffernan; Matthew J. Cohen; Thomas K. Frazer; Ray G. Thomas; Travis J. Rayfield; Jason Gulley; Jonathan B. Martin; Joseph J. Delfino; Wendy D. Graham (Limnology and Oceanography, 2010)
We use a long‐term chemical and hydrologic record in combination with longitudinal sampling and high‐frequency nitrate (NO 3 ‐ ) measurements from in situ sensors to describe temporal and spatial patterns of nitrogen (N) inputs and removal in the spring‐fed Ichetucknee River (Columbia County, Florida) and to determine the hydrological, geomorphic, and biological factors that influence those dynamics. Over a 20‐yr period of record, NO 3 ‐N removal averaged 118 kg N d ‐1 (0.77 g N m ‐2 d ‐1 ) over the upper 5 km of the Ichetucknee River. Three independent estimates of gross autotrophicNassimilation (from gross primary production, diel NO 3 ‐ variation, and standing biomass) agreed closely but accounted for less than 20% of observed N removal. Longitudinal surveys indicate negligible or negative dissolved organic nitrogen and ammonium (NH 4 + ) production, suggesting that denitrification is the predominant mechanism of N removal in this river. A positive relationship between discharge and the magnitude of NO 3 ‐N removal shows that interactions with the surrounding floodplain exert considerable influence at high flows, and longitudinal NO 3 ‐ patterns indicate that N removal may be influenced by channel morphology. These results suggest a greater role for dissimilatory processes and hydrologic connectivity with hyporheic and floodplain sediments than has been previously recognized in highly productive spring‐fed rivers of north Florida. While hydrologic variation is the primary determinant of variation in NO 3 ‐ removal within the Ichetucknee River, comparison across systems indicates that biotic characteristics can cause significant deviation from predictions based on purely physical models of relationships between river size and N removal.

The Q-type C2H2 zinc finger subfamily of transcription factors in Triticum aestivum is predominantly expressed in roots and enriched with members containing an EAR repressor motif and responsive to drought stress - Jason Kam; Peter M. Gresshoff; Ray Shorter; Gang-Ping Xue (Plant Molecular Biology, 2008)